2016
DOI: 10.3109/09638288.2015.1123308
|View full text |Cite
|
Sign up to set email alerts
|

Ethics teaching in rehabilitation: results of a pan-Canadian workshop with occupational and physical therapy educators

Abstract: Purpose: Ethical practice is an essential competency for occupational and physical therapists.However, rehabilitation educators have few points of reference for choosing appropriate pedagogical and evaluation methods related to ethics. The objectives of this study were to: 1) identify priority content to cover in ethics teaching in occupational therapy (OT) and physical therapy (PT) programs and 2) explore useful and innovative teaching and evaluation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…Ils sont à la recherche de tels résultats pour nourrir la réflexion éthique sur la pratique de la profession, et il en est de même des ergothérapeutes. L'éducation à l'éthique n'étant obligatoire que depuis 2008 au Canada (Drolet, 2014), peu d'ergothérapeutes ont eu, à ce jour, accès à une formation éthique (Hudon et al, 2016). Plus encore, l'enseignement de l'éthique dans les universités canadiennes est souvent confondu avec celui de la déontologie professionnelle (Bushby et al, 2015), laquelle réfère à l'ensemble des obligations professionnelles à l'égard des patients et de la profession telles qu'elles sont énoncées dans un code de déontologie (Drolet, 2014 (Drolet & Désormeaux-Moreau, 2015;Drolet & Goulet, sous presse;Drolet & Sauvageau, 2016), plusieurs éléments discutés dans cette section sont similaires, sans être identiques, à des éléments aussi précisés dans les sections de ces écrits consacrées aux méthodes utilisées dans cette recherche afin de répondre aux questions à l'origine de l'étude.…”
Section: Forces Et Limites De L'étudeunclassified
“…Ils sont à la recherche de tels résultats pour nourrir la réflexion éthique sur la pratique de la profession, et il en est de même des ergothérapeutes. L'éducation à l'éthique n'étant obligatoire que depuis 2008 au Canada (Drolet, 2014), peu d'ergothérapeutes ont eu, à ce jour, accès à une formation éthique (Hudon et al, 2016). Plus encore, l'enseignement de l'éthique dans les universités canadiennes est souvent confondu avec celui de la déontologie professionnelle (Bushby et al, 2015), laquelle réfère à l'ensemble des obligations professionnelles à l'égard des patients et de la profession telles qu'elles sont énoncées dans un code de déontologie (Drolet, 2014 (Drolet & Désormeaux-Moreau, 2015;Drolet & Goulet, sous presse;Drolet & Sauvageau, 2016), plusieurs éléments discutés dans cette section sont similaires, sans être identiques, à des éléments aussi précisés dans les sections de ces écrits consacrées aux méthodes utilisées dans cette recherche afin de répondre aux questions à l'origine de l'étude.…”
Section: Forces Et Limites De L'étudeunclassified
“…Ethics educators from across Canada also identified foundational ethics knowledge grounded in realistic practice examples as a priority for ethics teaching in occupational therapy (Hudon et al, 2016). However, although ethics education has evolved over the last 15 years, concerns persist regarding the development of relevant content, evidence-based teaching tools, and evaluation methods (Hudon et al, 2016;Jensen, Brasic-Royeen, & Purtilo, 2010;Kinsella & Bidinosti, 2016;Kinsella, Phelan, Park-Lala, & Mom, 2015;Laliberté et al, 2015). A recent study of a new online ethics education module for occupational therapy clinician-educators found that ethics knowledge cultivated via viewing the online module led to increased confidence in their ability to make, enact, explicate, and defend ethical decisions (VanderKaay, Letts, Jung, & Moll, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Ethics educators from across Canada also identified foundational ethics knowledge grounded in realistic practice examples as a priority for ethics teaching in occupational therapy (Hudon et al, 2016). However, although ethics education has evolved over the last 15 years, concerns persist regarding the development of relevant content, evidence-based teaching tools, and evaluation methods (Hudon et al, 2016; Jensen, Brasic-Royeen, & Purtilo, 2010; Kinsella & Bidinosti, 2016; Kinsella, Phelan, Park-Lala, & Mom, 2015; Laliberté et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dans cette perspective, l'ergothérapeute est amené à revendiquer auprès des assureurs une réponse adéquate aux besoins du patient, en collaboration avec ce dernier. Dans le contexte actuel où les ergothérapeutes sont peu formés à l'éthique [34], plus de formations devraient être prodiguées aux ergothérapeutes pour soutenir le développement de leurs compétences éthiques, lesquelles devraient inclure des compétences relatives à la défense des droits et intérêts des patients [35].…”
Section: éThique Des Vertusunclassified